1992
DOI: 10.1016/0266-7681(92)90008-p
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Fractures of the Scaphoid: the Value of Comparative X-rays of the Uninjured Wrist

Abstract: Pain or tenderness in the anatomical snuff-box following trauma suggests an injury to the scaphoid or surrounding soft tissues. It is often difficult to make a definite diagnosis since normal bone markings across the scaphoid can be misinterpreted as a fracture. To clarify whether a fracture is present or not, an X-ray of the uninjured scaphoid is taken in a comparable position to the most suspicious view. If bone markings are similar on both views, then a fracture can be excluded. Conversely, if the bone mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, the amount of trabecular and bone formation reported to whole the bone and the exact moment when a radiological follow-up should be conducted remain controversial [ 22 ]. It is known that XR displays a poor inter-observer agreement, which is not improved by clinical experience concerning scaphoid fracture detection [ 24 ]. In the early post-trauma period, Dias et al demonstrated that XR cannot be used to identify scaphoid consolidation due to the difficulty of identifying the trabecular crossing of the fracture and sclerosis of the fracture line in the context of the shape and orientation of the scaphoid bone [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the amount of trabecular and bone formation reported to whole the bone and the exact moment when a radiological follow-up should be conducted remain controversial [ 22 ]. It is known that XR displays a poor inter-observer agreement, which is not improved by clinical experience concerning scaphoid fracture detection [ 24 ]. In the early post-trauma period, Dias et al demonstrated that XR cannot be used to identify scaphoid consolidation due to the difficulty of identifying the trabecular crossing of the fracture and sclerosis of the fracture line in the context of the shape and orientation of the scaphoid bone [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of a so-called “carpal box” to provide magnified radiographs of the carpus may increase interobserver agreement in the interpretation of standard 4-view radiographs from 36% to 55% 50,51 , although this is not routinely utilized. Comparative views of the contralateral uninjured wrist also have been described 52 .…”
Section: Imagingmentioning
confidence: 99%